Dynamics of telomere length in captive Siamese cobra (Naja kaouthia) related to age and sex - Singchat, Worapong (Ecol Evol, 2019)
Telomeres comprise tandem repeated DNA sequences that protect the ends of chromosomes from deterioration or fusion with neighboring chromosomes, and their lengths might vary with sex and age. Here, age‐ and sex‐related telomere lengths in male and female captive Siamese cobras (Naja kaouthia) were investigated using quantitative real‐time polymerase chain reaction based on cross‐sectional data. A negative correlation was shown between telomere length and body size in males but not in females. Age‐related sex differences were also recorded. Juvenile female snakes have shorter telomeres relative to males at up to 5 years of age, while body size also rapidly increases during this period. This suggests that an accelerated increase in telomere length of female cobra results from sex hormone stimulation to telomerase activity, reflecting sexually dimorphic phenotypic traits. This might also result from amplification of telomeric repeats on sex chromosomes. By contrast, female Siamese cobras older than 5 years had longer telomeres than males. Diverse sex hormone levels and oxidative stress parameters between sexes may affect telomere length.